KINERJA DAYA SAING TEH HIJAU INDONESIA DI PASAR INTERNASIONAL - Muhammad Ali Yafi; Amanda Sekar Adyanti (Universitas Sebelas Maret, 2024)
Tea commodity is one of the export commodities that can contribute to the Gross Domestic Product (GDP) of Indonesian plantations. Indonesia’s tea production fluctuates but tends to decline, resulting in declining tea exports. Indonesia’s tea production is dominated by 78% black tea, 20% green tea, and the remaining 2% other types of tea. Although green tea has lower exports than black tea, Indonesia’s green tea market share has a better market share. The purpose of the study was to determine the comparative and competitive competitiveness of green tea exports, as well as the position of Indonesia’s green tea export competitiveness (HS 090220) in the international market. The data used starts from 2011-2022 with 6 destination countries namely Poland, Germany, Taipei, Pakistan, Malaysia, and China. The analysis used is RCA (Revealed Comparative Advantage), EPD (Export Product Dynamic), and ISP (Trade Specialisation Index) analysis. The results of the analysis showed that Poland has the highest RCA value of 29.99 and followed by Germany, Taipei, Pakistan, and China which have strong competitiveness. While Malaysia has a weak competitiveness with an RCA value of 0.34. The results of the EPD analysis obtained that Poland is in the Rising Star position which means that Indonesian green tea has a competitive advantage and is experiencing a positive increase in market share, while China and Pakistan are in the Lost Opportunity position. Malaysia is located in the Retreat position, which means that Indonesian green tea does not have a competitive advantage, while Germany and Taipei are in the Falling Star position. ISP results obtained Indonesia as an exporter country and has a strong competitive position in Pakistan. Indonesia as an importer country and has a weak competitive position in China.